Spatially composition-modulated two-dimensional WS2xSe2(1−x) nanosheets. Issue 14 (22nd March 2017) - Wu, Xueping; Li, Honglai; Liu, Hongjun; Zhuang, Xiujuan; Wang, Xiao; Fan, Xiaopeng; Duan, Xidong; Zhu, Xiaoli; Zhang, Qinglin; Meixner, Alfred J.; Duan, Xiangfeng; Pan, Anlian
Abstract : The growth of spatially composition-modulated 2D WS2 x Se2(1− x ) nanosheets and WS2 –WS2 x Se2(1− x ) lateral heterostructures is realized for the first time. Abstract : Controllable synthesis of two-dimensional (2D) transition-metal dichalcogenides (TMDs) with tunable bandgaps is vital for their applications in nanophotonics, due to its efficient modulation of the physical and chemical properties of these atomic layered nanostructures. Here we report for the first time, the controllable synthesis of spatially composition-modulated WS2 x Se2(1− x ) nanosheets and WS2 –WS2 x Se2(1− x ) lateral heterostructures by a developed one-step chemical vapor deposition (CVD) approach, as well as the understanding of their growth mechanism. During the growth, the composition was optically tuned along the plane of the atomic layered nanosheets through the precise control of evaporation sources. Microstructure characterization confirms the chemical identity of the composition modulated nanosheets, with S and Se contents gradually converting from the center to the edge. Local photoluminescence (PL) and Raman studies further demonstrate the position-dependent optical properties of the as-grown nanosheets, with the PL peak and Raman modes shifting in a wide range along the whole plane of the nanostructures, which are consistent with their tunable compositions and bandgaps. This demonstration of composition-modulated nanostructures provides a beneficial approach for the preparation of 2D semiconductor heterostructures and may open up a wide range of applications in nanoelectronics and optoelectronics.